Infrastructure in Latin America and the Caribbean : Recent Developments and Key Challenges - Fay, Marianne (Washington, DC: World Bank, 2012)
This book reviews Latin America's experience with infrastructure reform over the last fifteen years. It argues that the region's infrastructure has suffered from public retrenchment and unrealistic expectations about private involvement. Poor infrastructure now hampers productivity, growth, and poverty reduction. Addressing this requires more and better spending, and acceptance that governments remain central to infrastructure provision and supervision, although the private sector still has an important role to play.